Measuring credit structure impact on economic growth in Croatia using (VECM) 1990-2018 - Škare, Marinko; Sinković, Dean; Porada-Rochoń, Małgorzata (Journal of Business Economics and Management, 2019)
Studies on the finance-growth link use different proxy variables for financial development. Among the most used is the total credit share in the GDP. Previous empirical studies show to be sensitive to the choice of the finance proxy indicator. Total credit share in the GDP appears biased in empirical modeling. Credit structure (loans to firms and households) prove to be more robust when used in the modeling. Credit structure reveals a different impact on economic growth showing lending policy impact varies depending on the credit structure. Researchers studying the finance-growth link must account for this when investigating supply leading and demand-following theories. Policymakers should also take care of the credit structure since loans to household discourage growth in the long run and are sensitive to economic shocks. We find empirical evidence to support both supply leading and demand- following theory. Bi-directional causality between private loans to firms/households and economic growth exists using Granger causality test. Private loans to firms and households economic growth exists using Granger causality test. Private loans to firms and households have a positive impact on economic growth in Croatia.